The Abdomen in "Thoracoabdominal" Cannot Be Ignored: Abdominal Compartment Syndrome Complicating Extracorporeal Life Support. (8th May 2014) - Lee, Arthur J.; Wells, Bryan J.; Chun, Rosaleen; Ball, Chad G.; Kirkpatrick, Andrew. W.
Abstract : Extracorporeal life support (ECLS) is an incredible life-saving measure that is being used ever more frequently in the care of the critically ill. Management of these patients requires extreme vigilance on the part of the care providers in recognizing and addressing the complications and challenges that may arise. We present a case of overt abdominal compartment syndrome (ACS) in a previously well young male on ECLS with a history of trauma, submersion, hypothermia, and no intra-abdominal injuries. The patient developed ACS soon after ECLS was initiated which resulted in drastically compromised flow rates. Taking into account the patient's critical status, an emergent laparotomy was performed in the intensive care unit which successfully resolved the ACS and restored ECLS flow. The patient had an unremarkable course following and was weaned off ECLS but unfortunately died from his original anoxic injury. This case highlights several salient points: first, care of patients on ECLS is challenging and multiple etiologies can affect our ability to manage these patients; second, intra-abdominal pressures should be monitored liberally in the critically ill, especially in patients on ECLS; third, protocols for emergent operative treatment outside of traditional operating rooms should be established and care providers should be prepared for these situations.